Second Thoughts on the Proposition ＂Literature Is the Study of Man - Weiqin, Liu (Social sciences in China, 2011)
钱谷融先生在20世纪五十年代撰文指出，高尔基建议把文学叫做"人学"，于是认为最早提出"文学是人学"命题的是高尔基；进入21世纪后，钱先生又说，"文学是人学"的发明权应归属于泰纳。本文认为：事实上，高尔基未曾提出过"文学是人学"的建议，泰纳也没有作过"文学是人学"的完整表达。不过，尽管如此，钱谷融先生在20世纪五十年代的政治与文学生态中，能提出"文学是人学"的命题，并阐释文学的"人性"品格，这既需要勇气，也需要才情，更具有非凡的意义。因此，在后来半个多世纪的文学创作和研究中，这一提法产生了极其巨大的积极影响和作用。不过，也应该看到，"文学是人学"这一命题缺乏其自圆其说的学理性依据，尤其站在新的世纪，以更高的标准对这一命题进行审视，其存在的局限性也是较为明显的，这就是：人是文学描写的中心，而不是文学描写对象的全部；人是评价文学的一个尺度，并不是评价文学的唯一尺度。文学还应遵循文学自身的特殊规律。 关键词: "文学是人学" 来源 时代背景 关系图式 In an essay written in the 1950s, Qian Gurong noted that Gorky once suggested calling literature "the study of man." He went on to argue that Gorky was the first to have put forward this proposition. In the twenty-first century, Qian added the comment that "Rights to the statement 'Literature is the study of man' should go to H. Taine." In this paper, I argue that in fact, Gorky never suggested calling literature "the study of man," nor did Taine ever say in so many words "Literature is the study of man." Nevertheless, it certainly took extraordinary courage and talent for Qian Gurong to have put forward this proposition and expounded on the "humane" character of literature given the political and literary situation of China in the 1950s. His act was of more than usual significance, for it had an enormously positive influence on literary creation and research in the succeeding half century. At the same time, it is worth noting that the proposition "Literature is the study of man" is not justifiable in terms of the principles of logic. In the new century, as we examine this proposition more rigorously, we can see its deficiencies more clearly: that is, man is the center, rather than the sole object, of literary description; man is a measure, rather than the sole measure, of literary criticism. Besides, literature should follow its own particular laws.